The Effect of Role-Playing Methods on Early Childhood Social-Emotional Development - Irmayanti, Irmayanti; Rusmayadi, Rusmayadi; Musi, Muhammad Akil; Halik, Abdul (PT. Riset Press International, 2025)
This research is a quantitative study using an experimental method. The research design employed is a one-group pretest-posttest aimed at (1) determining the social skills of children in Group B at KB Al-Qalam before the role-playing method is applied, (2) determining the socio-emotional skills of children in Group B at KB Al-Qalam after the role-playing method is applied, and (3) analyzing whether there is an influence of the role-playing method on the socio-emotional development of early childhood children in Group B at KB Al-Qalam. The independent variable in this study is the role-playing method, while the dependent variable is the socio-emotional skills of the children. The sample in this study consists of all children in Group B at KB Al-Qalam, totalling 15 children. The data obtained from the research show that (1) the social skills of children in Group B at KB Al-Qalam before the role-playing method was applied were in the very low category, with a percentage of 60%, (2) the socio-emotional skills of children in Group B at KB Al-Qalam after the role-playing method was applied were in the moderate category, with a percentage of 33%, and (3) there is an influence of the role-playing method in developing the socio-emotional skills of children in Group B at KB Al-Qalam.